Promotion of environmental education in the papelón community (Revista Electrónica REDINE, 2018)
Conventional agroproductive practices cause ecological deep crisis on a planetary scale, creating that new challenges is facing for scientific, like necessity of evaluate ecologically, the efficiency of systems of agricultural production, in an sustainability context. Agroecology like ecological approach of agricultural process, not only include food production, but keep in mind cultural, social and economic aspects. In this regard, it statement like objectives promote the environment education by technology transfer of agroecologycal production in Papelón community, Lara state. Counted with the participation of 10 families, in elaborating of a demonstrative garden and organic waste recycling. Teachers and workers personal of Unidad Educativa “Escuela Bolivariana Omaira Mendoza de Escobar” were involved in activities in a school garden with de children that belong to the school. In the technology transfer cooperate students of community service of Programme Agronomy Engineering, Agronomy and Veterinary School (UCLA). Was achieved to promote environment education through technology transfer of agroecologycal production, in topics like demonstrative families garden and scholar, as well as organic solids waste recycling in order to reduce costs due chemistry fertilization and mitigate environment impact due to excessive use nitrogen and phosphate fertilizer that pollutes soils and water. University has important role in promoting environment education through agroecologycal technology transfer in line with sustainable development of rural community.
Keywords: demonstration garden; recycling; students